Benefit-Cost Ratio and Payback Period of Palm Oil Plantation Business in Kalimantan - Susanto, Anton; Kumalasari, Dwi Apriyanti (Universitas Syiah Kuala, 2025)
This study aims to analyze the cost structure and financial feasibility of oil palm farming in Buana Mustika Village, Telaga Antang Subdistrict, East Kotawaringin Regency. The research employed a qualitative approach using purposive sampling based on land size: 1.5 ha, 7.25 ha, and 25 ha. Data were collected through interviews, observations, and documentation, and analyzed using financial feasibility indicators such as R/C Ratio, B/C Ratio, NPV, IRR, and Payback Period. The results show that all scales of oil palm farming are financially feasible with R/C Ratios above 2 (ranging from 2.11 to 2.58), B/C Ratios greater than 1, and IRRs ranging from 50% to 81%. The payback period is achieved in less than 2 years. Additionally, contribution margins and NPV results are highly positive. The study concludes that oil palm farming in Buana Mustika Village is profitable and feasible for sustainable development.